On the Relation between Existential Philosophy and Religion. Heidegger’s Readings of Schleiermacher - Flamarique, Lourdes (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
Heidegger prepares the way for his hermeneutic-existential phenomenology by reading, among other texts, Schleiermacher’s writings. In Schleiermacher’s theological and philosophical thoughts, mainly in the explanation of religion and the relation between feeling and self-consciousness, some characteristics concepts of Heidegger can already be found. Following some notes and references by Heidegger, this article proposes a dialogue with both thinkers, that shows the continuity of Schleiermacher’s discussion on finitude, individuality and historicity of the existence along the lessons that Heidegger dictated in 1919 and 1920